Impact of Tropical Cyclones on Food and Nutrition Security: A Global Scoping Review and Thematic Analysis - Chiotha, Patience M; Haryanto, Budi (UI Scholars Hub, 2026)
The increasing frequency and intensity of tropical cyclones driven by climate change pose growing threats to food and nutrition security. Globally, an estimated 80–90 tropical cyclones occur annually, affecting approximately 119 million people. Evidence regarding their impact on food systems, dietary patterns, and nutritional status remains fragmented. This scoping review aimed to map global evidence on the impacts of tropical cyclones on food and nutrition security, identify key pathways of impact, and examine affected indicators at household and individual levels. The review followed Joanna Briggs Institute guidelines and PRISMA-ScR. Searches were conducted in PubMed/MEDLINE, Web of Science, Scopus, and Google Scholar for peer-reviewed articles published between 2015 and 2025. Eligible studies reported food security, dietary, or nutritional outcomes following cyclone events. Data were extracted and thematic analysis identified common impact pathways. Twelve studies from Asia, Africa, the Caribbean, the Pacific, and the United States were included. Tropical cyclones were associated with reduced food availability and access, damage to water and sanitation systems, declining household income, increased reliance on food aid, and reduced dietary diversity. Reported nutrition outcomes included low mid-upper arm circumference and body mass index among women and children, as well as elevated rates of stunting and underweight. Governance challenges and social inequalities further exacerbated food and nutrition insecurity. Overall, tropical cyclones undermine food and nutrition security through interconnected environmental, economic, and social pathways, highlighting the need for climate-resilient food systems and nutrition-sensitive disaster responses. Keywords: Tropical cyclones, Food security, Nutrition security, Climate change, Malnutrition